How Transgender Minority Groups Communicate with the Majority Society in Indonesia - Safitri, Faiza Hanna; Utari, Prahastiwi; Sudarmo, Sudarmo (PT FORMOSA CENDEKIA GLOBAL, 2024)
This qualitative descriptive research will critically analyze abouthow people in minority groups choose different ways to eliminate or overcome stereotypes on transgender issues and try to build good relations with dominant groups in order to be accepted in their environment. studied at the level of co-cultural communication theory by Mark Orbe.Information was obtained through informant interview techniques from the largest transgender community in Indonesia. The research results show that transgender groups in Indonesia still experience violence, discrimination and do not have a safe space. Minority groups have succeeded in adapting by using non-assertive communication methods in the majority community environment.